2020
DOI: 10.1519/jpt.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

Hip Muscle Strengthening for Knee Osteoarthritis: A Systematic Review of Literature

Abstract: Background and Purpose: Osteoarthritis (OA) of the knee joint results in chronic pain and functional decline among older adults. Hip muscle weakness has been observed in persons with knee OA and is claimed to increase the medial compartment loading on the knee joint. Although individual studies are available, no review has yet integrated the literature on the benefits of hip muscle strengthening for persons with knee OA. This review aims to systematically summarize the current evidence on the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 49 publications
0
23
0
1
Order By: Relevance
“…Pain is the main symptomatic manifestation of osteoarthritis of the knee, and effective control of joint pain in patients is crucial to improve their survival quality. It has been pointed out in a study that herbal treatment can better control joint pain [ 21 23 ]. In this study, the VAS, JOA, and AIMS2-SF scores of patients were analyzed, and the results showed that the VAS scores of the experimental group were lower than those of the control group after treatment, and the JOA and AIMS2-SF scores were higher than those of the control group ( P < 0.05), suggesting that the combined treatment with clearing heat and dispelling paralysis soup could better control the joint pain of patients and improve their survival quality.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is the main symptomatic manifestation of osteoarthritis of the knee, and effective control of joint pain in patients is crucial to improve their survival quality. It has been pointed out in a study that herbal treatment can better control joint pain [ 21 23 ]. In this study, the VAS, JOA, and AIMS2-SF scores of patients were analyzed, and the results showed that the VAS scores of the experimental group were lower than those of the control group after treatment, and the JOA and AIMS2-SF scores were higher than those of the control group ( P < 0.05), suggesting that the combined treatment with clearing heat and dispelling paralysis soup could better control the joint pain of patients and improve their survival quality.…”
Section: Discussionmentioning
confidence: 99%
“…Strong and high-quality evidence recommends strengthening the muscles of the hip and knee in the conservative treatment of people with knee OA. 68 70 In PFOA, there is a lack of randomized clinical trials on the effects of a program to strengthen the muscles of the lower limb. However, the results of a pilot feasibility study suggest that hip strengthening and a core stabilization program may be beneficial in improving symptoms, function, and physical performance in people with PFOA.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, a review study showed that muscle strength training around the hip joint can effectively improve the lower limb function and biomechanical measures of the knee in patients with chronic knee pain. A systematic review identified strong and high-quality evidence to recommend hip muscle strengthening in the conservative management of patients with knee OA (Raghava et al, 2020 ). The exercise program of this study also paid special attention to the ideal training of the muscles around the hip joint.…”
Section: Discussionmentioning
confidence: 99%